Overview of difficulties and material identification of chemical bonds based on multiple representations: Teacher’s view - Widarti, Hayuni Retno; Wiyarsi, Antuni; Yamtinah, Sri; Shidiq, Ari Syahidul; Sari, Meyga Evi Ferama; Fauziah, Putri Nanda; Natasya, Shella; Khandi, Cahya Aulia; Rokhim, Deni Ainur (Eclética Química, 2025)
Chemical bonding involves three levels of representation, namely macroscopic, submicroscopic, and symbolic, which are often difficult for students to understand due to their abstract and complex concepts. In this case, teachers play an important role as facilitators. However, teachers still experience various challenges in applying a multiple representation approach. This study aims to identify and analyze the difficulties in multi-representation-based chemical bonds based on the views of several chemistry teachers. A total of 14 open and closed question items via Google Forms were distributed online. Based on a survey of several chemistry teachers, the most difficult sub-material in chemical bonds is molecular geometry, while the easiest is ionic bonds. Chemistry teachers participating in this study tend to focus more on symbolic, macroscopic, and submicroscopic representations in teaching chemical bonds.